(untitled) - Sadd, Martin H (Amsterdam ; Boston, 2005)
Reference: p. 456; 2 parts (15 chapters): Foundation and elementary applications; advanced application
Keywords: Elasticity; Vật lý -- Lý thuyết đàn hồi